Myoung-Sun Song. 2019. Hanguk Hip Hop, Global Rap in South Korea. - Oh, Hyun Joo Sandy (Journal of World Popular Music, 2021)
Myoung-Sun Song. 2019. Hanguk Hip Hop, Global Rap in South Korea. Cham, Switzerland: Palgrave Macmillan. ix + 198 pp. ISBN 978-3-030-15696-1 (hbk)